1997
DOI: 10.1164/ajrccm.155.2.9032181
|View full text |Cite
|
Sign up to set email alerts
|

Prone position in mechanically ventilated patients with severe acute respiratory failure.

Abstract: The purpose of this study was to characterize changes in oxygenation, expressed as PaO2/F(I)O2, when patients with severe acute respiratory failure (PaO2/F(I)O2 < 150), unrelated to left ventricular failure to atelectasis, were turned to and from a supine to prone position at 1- and 4-h intervals. Ventilator settings were unchanged. Thirty-two consecutive patients were studied 1 h before, 1 and 4 h during and 1 h after placing in a prone position with PaO2/F(I)O2 of 103 +/- 28, 158 +/- 62, 159 +/- 59, and 128 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
163
0
25

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(197 citation statements)
references
References 18 publications
9
163
0
25
Order By: Relevance
“…In ARDS patients not responding to recruitment manoeuvres, Grasso et al found that a decreased chest wall compliance limited the transpulmonary gradient, and hence the driving force for recruitment [57], a mechanism likely to explain the failure of recruitment manoeuvres in non-responders in other studies [61,70,71]. Pelosi et al observed that patients with primary ARDS were less responsive to a recruitment manoeuvre [61], which is in concordance with the experimental studies by Kloot et al mentioned before [31].…”
Section: Human Studiessupporting
confidence: 56%
“…In ARDS patients not responding to recruitment manoeuvres, Grasso et al found that a decreased chest wall compliance limited the transpulmonary gradient, and hence the driving force for recruitment [57], a mechanism likely to explain the failure of recruitment manoeuvres in non-responders in other studies [61,70,71]. Pelosi et al observed that patients with primary ARDS were less responsive to a recruitment manoeuvre [61], which is in concordance with the experimental studies by Kloot et al mentioned before [31].…”
Section: Human Studiessupporting
confidence: 56%
“…The consistently quoted response rate is approximately 70%. 38 The more even distribution of trans-alveolar pressure accomplished by the prone-modified chest wall may reduce the impact of stress focusing at the junctions of closed and open alveoli, 39 reduce the tendency for airway opening and closure, allow the use of less PEEP, improve afterload to the right ventricle, 40,41 and permit reduction of potentially toxic concentrations of inspired oxygen. To achieve a survival benefit, it would appear from published data that the patient should be positioned prone for the majority of the day for at least several days.…”
Section: Prone Positioning As a Standard For Ards-promentioning
confidence: 99%
“…This value was chosen on the basis of the literature, in which other authors have used changes of 10 to 20% in this ratio, or an absolute improvement of 20 mmHg in PaO 2 , to define which patients were responders to PP. 6,7,17,23,27 Using this figure of 15%, most of our patients (78.0%) did improve their oxygenation in PP as early as 30 minutes after the maneuver (65.85% of all patients). Moreover, 62.5% had a continuing response even after changing back to SP.…”
Section: Discussionmentioning
confidence: 70%